Baby SPA Relationship With Baby Weight Changes In PMB Herviza - Fatimah sari; Lili Yuliana Tambunan; Rodinih, Rodinih; Ni Nyoman Widya Pradani (Sean Institute, 2024)
Background: low birth weight babies (LBW) is oneof the causes of infant mortality in Indonesia. The purpose of this study was to determine the relationship of infant massage to weight gain in lbw infants. Type of analytical survey research with cross sectional design. Subjects consisted of infants who were given massage treatment and infants who were not given treatment. The total sample of 36 babies who were massaged. Data collection is taken from the documentation sheet of medical records in PMB Herviza. Data analysis using Chi-Square. The characteristics of the baby in the massage is the weight before the massage and weight after the massage and the characteristics of the baby who is not in the massage is the initial weight and weight after 1 month. The results of Pearson Chi-Square value is 40.783 by comparing using the confidence level ③ = 0.05, the results of X2 table is 3.84146 so that the results obtained are X2 count > x2 table (40.783 > 3.84146). Based on the value of significance obtained, it can also be seen that the X2 count of 0.000 < the value of ③ =0.05. There is a relationship between infant massage to weight gain in infants with low birth weight category based on the results of OR = 5,500. Babies who are massaged have the potential to gain weight >140 grams 5.5 times greater than those who are not massaged.